Analisis Love Language dalam Menjaga Keharmonisan Rumah Tangga Perspektif Hukum Islam: Studi Kasus Pasangan Menikah pada Usia Pernikahan 0-5 Tahun di Desa Taman Fajar - Andri Ratama; Nurnazli; Jayusman (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The fulfillment of love language is the duty of both husband and wife. However, the reality is that this rationale is not understood and known by all levels of society. Based on initial interviews that researchers have conducted with several subjects from married couples aged 1-5 years in Taman Fajar village. Many couples have done the language of love that is meant in the theory of love language, but they are not fully aware of what they are doing including the language of love as conveyed by Chapman so that many of them do not know what love language their partner has, so that it has an impact on the emergence of domestic conflict. Seeing the lack of love language that is difficult for couples to express can lead to divorce in marriages of less than the first five years, and this is the reference for researchers to choose the topic. The purpose of this study is how the application of love language in maintaining household harmony in married couples at the age of marriage 0-5 years and how Islamic Family Law views the application of love language in maintaining household harmony in married couples at the age of marriage 0-5 years in Taman Fajar Village, Purbolinggo District, East Lampung Regency. The method used in this research is a qualitative method in which the author conducts interviews, documents and field observations. The results obtained in this study are the application of love language or love language carried out with the aim of perfecting communication in order to maintain family integrity or harmony in the household. The application of love language or love language that is intertwined by respondents is not only verbal but also equipped with non-verbal communication. In the review of Islamic family law (syakinah family), the application of love language provides many benefits such as increasing harmony in the household, increasing family resilience in preventing conflict, husband and wife need each other and complement each other, and the association of husband and wife in a good way (mu'asyarah bil ma'ruf).